AVALIAÃ‡ÃƒO DA â€œTERRA DE QUIXABEIRAâ€ (Bumelia sertorium L.) NO MELHORAMENTO DA QUALIDADE DO SOLO - Silva, Adilson Nunes da; Santos, Ailton Mascarenhas dos; Bortolotto, Rafael Pivotto; Olinda, Ricardo Alves de; Carvalho, JosÃ© Carlos Ribeiro de; Reichardt, Klaus (REVISTA DE AGRICULTURA, 2016)
AVALIAÃ‡ÃƒO DA â€œTERRA DE QUIXABEIRAâ€ (Bumelia sertorium L.) NO MELHORAMENTO DA QUALIDADE DO SOLO